PC.14 Adjustment of directly measured adipose tissue volume in infants. (9th June 2014) - Gale, C; Santhakumaran, S; Wells, JCK; Modi, N
Abstract : Background: Direct measurement of adipose tissue using magnetic resonance imaging (MRI) is increasingly used to characterise body composition. Optimal techniques for adjusting direct measures of infant adipose tissue remain to be determined. Objectives: To explore the relationships between body size and directly measured total and regional adipose tissue volume (ATV), and the relationship between ATV depots representing the metabolic load of adiposity, to determine optimal methods of adjusting adiposity in infancy. Design: Analysis of regional ATV measured using MRI in longitudinal and cross-sectional studies. Subjects: Healthy term infants; 244 in the first month (1–31 days), 72 in early infancy (42–91 days). Methods: The statistical validity of commonly used indices adjusting adiposity for body size was examined. Valid indices, defined as mathematical independence of the index from its denominator, to adjust ATV for body size and metabolic load of adiposity were determined using log-log regression analysis. Results: Indices commonly used to adjust ATV are significantly correlated with body size. Most regional AT depots are optimally adjusted using the index ATV/(height) 3 in the first month (Figure 1 ) and ATV/(height) 2 in early infancy. Internal abdominal (IA) ATV was optimally adjusted for subcutaneous abdominal (SCA) ATV by calculating IA/SCA 0.6 (Figure 2 ). Conclusions: Commonly used methods of adjusting adipose tissue in early infancy, such as percentage adipose tissue, have statistical limitations. We describe statistically optimal indices for adjusting directly measured adipose tissue volume for body size and to represent the metabolic load of adiposity in early infancy.